1)
[tex]6+4(3-x)=3(-2x+9)\\\\6+12-4x=-6x+27\\\\18-4x=-6x+27\\\\-4x+6x=27-18\\\\2x=9\ /\ :\ 2\\\\x=4,5[/tex]
spr.
[tex]L=6+4\cdot(3-4,5)=6+4\cdot(-1,5)=6-6=0\\\\P=3\cdot(-2\cdot4,5+9)=3\cdot(-9+9)=3\cdot0=0\\\\L=P[/tex]
2)
[tex]8(x-2)-5=4-3(x+1)\\\\8x-16-5=4-3x-3\\\\8x-21=-3x+1\\\\8x+3x=1+21\\\\11x=22\ /\ :\ 11\\\\x=2[/tex]
spr.
[tex]L=8\cdot(2-2)-5=8\cdot0-5=0-5=-5\\\\P=4-3\cdot(2+1)=4-3\cdot3=4-9=-5\\\\L=P[/tex]
3)
[tex]4-(8-2x)=3(x+2)\\\\4-8+2x=3x+6\\\\2x-4=3x+6\\\\2x-3x=6+4\\\\-x=10\ /\ \cdot\ (-1)\\\\x=-10[/tex]
spr.
[tex]L=4-(8-2\cdot(-10))=4-(8+20)=4-28=-24\\\\P=3\cdot(-10+2)=3\cdot(-8)=-24\\\\L=P[/tex]
4)
[tex]\frac{6-x}{2}=0,5x\ /\ \cdot\ 2\\\\6-x=x\\\\-x-x=-6\\\\-2x=-6\ /\ :\ (-2)\\\\x=3[/tex]
spr.
[tex]L=\frac{6-3}2=\frac32=1\frac12\\\\P=0,5\cdot3=1,5=1\frac12\\\\L=P[/tex]